Association Between Inflammatory Mediators and Pulmonary Blood Flow in a Rabbit Model of Acute Pulmonary Embolism Combined With Shock - Wang, Yuting; Yu, Delong; Yu, Yijun; Liu, Xiaoyan; Hu, Liqun; Gu, Ye (Frontiers in Physiology, 2020)
Background The pro-inflammatory cytokines were detected in pulmonary embolism (PE) and non-pulmonary embolism (non-PE) tissues to explore the role of inflammation responses and their relationship with the pulmonary blood flow in a rabbit model of acute pulmonary embolism combined with shock. Methods and Results Nineteen rabbits were randomly divided into sham operation group (S group, n=8) and massive PE (MPE group, n=11). MPE model was established by injecting the autologous blood clots into the main pulmonary artery of rabbit. Pulmonary angiography showed that the pulmonary circulation time was significantly prolonged in MPE group, and pulmonary blood flow was attenuated at 120 min post PE. hematoxylin-eosin (HE) staining revealed enhanced inflammatory cells infiltration around the pulmonary vessels in PE and non-PE tissues, and obvious edema on perivascular region. Meanwhile, the expressions of inducible nitric oxide synthase (iNOS) and arginase 1 (Arg-1) in pulmonary vascular and alveolar tissues were significantly upregulated and iNOS/Arg-1 ratio was significantly higher in MPE group than in S group. Moreover, the levels of tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β) were also significantly increased in PE and non-PE tissues, and interleukin-6 (IL-6) level was significantly increased in non-PE tissues in MPE group as compared to S group. Thromboxane A2 (TXA2) and alpha smooth muscle actin (α-SMA) levels were significantly higher in both PE and non-PE tissues in MPE group than in S group. Conclusions Activation of inflammation mediators in PE and non-PE tissues might be one of the crucial factors responsible for pulmonary vasculature constriction and pulmonary blood flow attenuation in this MPE model.